The role of condom use self-efficacy on intended and actual condom use among university students in Ghana - Kwaku Oppong Asante; Paul Narh Doku; Osafo Joseph (University of Cape Coast, 2015)
Little attention has been paid to the dimensions that help to predict and understand condom use among university students within an African context. A cross-sectional study involving 518 university students in Accra, Ghana was conducted to determine how the Condom Use self-Efficacy Scale-Ghana (CUSES-G) can predict both actual condom use and future condom use. Of all the participants, 84 %were sexually active but less than half of the sample (48 %) reported to have used condom during their last sexual intercourse. A hierarchical regression analysis showed that components of the Condom Use Self-Efficacy Scale (CUESE-G) such as appropriation, assertiveness, pleasure and intoxication, and STDs predicted condom use and condom use intentions. Behavioural change campaigns targeting university students should encourage condom use self-efficacy, as this would strengthen condom use, which is economically cheap and practically effective means of preventing STIs including HIV.
Keywords: Condom use self-efficacy Ghana Sexually active University students